2021
DOI: 10.3390/ijerph18063004
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-Electrophysiological Benefits of Forest Therapies Focused on Qigong and Walking with Elderly Individuals

Abstract: We developed two distinct forest therapy programs (FTPs) and compared their effects on dementia prevention and related health problems for older adults. One was focused on Qigong practice in the forest (QP) and the other involved active walking in the forest (WP). Both FTPs consisted of twelve 2-h sessions over six weeks and were conducted in an urban forest. We obtained data from 25, 18, and 26 participants aged 65 years or above for the QP, WP, and control groups, respectively. Neuropsychological scores via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 74 publications
(100 reference statements)
0
26
0
Order By: Relevance
“…All professionally conducted forest therapy sessions followed the same program, thus the effect of different programs could not be investigated. In this respect, a recent Korean study performed with elderly individuals showed that forest therapy programs focused on Qigong or active walking produced specific neuropsychological and electrophysiological benefits, both beneficial for preventing dementia and relieving related health problems [ 77 ]. Moreover, the single session performed without professional guidance (FTS1) was affected by a low level of weather comfort, which could have played an important role in the respective insignificant results.…”
Section: Discussionmentioning
confidence: 99%
“…All professionally conducted forest therapy sessions followed the same program, thus the effect of different programs could not be investigated. In this respect, a recent Korean study performed with elderly individuals showed that forest therapy programs focused on Qigong or active walking produced specific neuropsychological and electrophysiological benefits, both beneficial for preventing dementia and relieving related health problems [ 77 ]. Moreover, the single session performed without professional guidance (FTS1) was affected by a low level of weather comfort, which could have played an important role in the respective insignificant results.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of physical activity in urban green spaces has also been studied in more ecological settings. Yi et al ( 96 ) investigated how two different “forest therapy” programs–active walking versus a resting control group–could impact elderly individuals. The results showed that active walking had an increase in alpha and beta values (from baseline).…”
Section: Resultsmentioning
confidence: 99%
“…As a whole, our neuroscientific evidence assists urban planners, organizations, and communities to increase green and blue spaces, considering their biodiversity and quality, within the urban infrastructure–as it potentiates neural mechanisms linked to mental restoration ( 82 ) and stress-recovery ( 49 , 108 , 112 ). Furthermore, supporting the access to local natural landscapes (such as wetlands and forests) provide positive cognitive and emotional feedback to both healthy and more vulnerable groups (e.g., the elderly population) ( 89 , 96 , 106 ). Furthermore, city planning should consider overcrowding as a potential stressor ( 17 ), and take into account the space behavior in relation to per capita area when designing urban built and natural spaces ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion of the before-and-after estimates of this study from the meta-analysis also substantially reduced statistical heterogeneity, which further supports the decision to present this study narratively. Another parallel-group study had three arms-forest walking, Qigong exercise program, and no intervention (Yi et al, 2021). However, as direct comparisons between the forest walking program and the Qigong program were not reported, we only considered the comparison between the forest walking program (which met the definition of an outdoor community ambulation intervention) and the "no intervention" comparison group.…”
Section: Discussionmentioning
confidence: 99%